2007
DOI: 10.1016/j.ecolmodel.2006.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of recruitment limitation and canopy disturbance on tropical tree species richness

Abstract: Intermediate disturbance hypothesis a b s t r a c tWe used the process-based forest growth model Formind2.0 to show that recruitment limitation and the intermediate disturbance hypothesis which proposes maximum diversity in forests of intermediate disturbance intensity or frequency are both processes which impact on tropical tree species richness. Both processes influence each other and should therefore not be analyzed separately. While on a local level a rise in recruitment limitation promotes species richnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The high species richness observed in D1 is because it is an area with highly disturbed community and large canopy gaps. This is similar to earlier observations that in natural conditions, disturbances either caused naturally or anthropogenically play an ideal role in enhancing the species richness (Köhler and Huth 2007). Hubbell et al (1999) studies on plant species richness at Barro Colorado Island, Panama show high species richness in the quadrants containing gaps than non-gap quadrants.…”
Section: Species Richnesssupporting
confidence: 82%
“…The high species richness observed in D1 is because it is an area with highly disturbed community and large canopy gaps. This is similar to earlier observations that in natural conditions, disturbances either caused naturally or anthropogenically play an ideal role in enhancing the species richness (Köhler and Huth 2007). Hubbell et al (1999) studies on plant species richness at Barro Colorado Island, Panama show high species richness in the quadrants containing gaps than non-gap quadrants.…”
Section: Species Richnesssupporting
confidence: 82%
“…As timber extraction is ubiquitously performed in the Zona Maya, this activity could slowly erode species richness until a threshold is reached in which plant diversity drops. The reduction in tree diversity could be associated with changes in canopy openness and the differential recruitment of species (Huth and Ditzer 2001;Köhler and Huth 2007). Under logging programs, this loss of species is a challenge for managers.…”
Section: Discussionmentioning
confidence: 98%
“…More specifically, if species are unable to reach all suitable patches in the landscape, species turnover among regenerating patches of forests may be higher than within undisturbed forest (Hubbell et al . ; Köhler & Huth ). However, this study found no difference in beta‐diversity between disturbed and control subplots in any site (Fig.…”
Section: Discussionmentioning
confidence: 99%